“Classical” liberalism in France, from the middle of the 19th century to World War I : Strengths and paradoxes of a thwarted society project - Andriot, Antonin (apropos [Perspektiven auf die Romania], 2023)
Why did “classical” liberalism – during its European golden age in the mid-19th century – never give birth, in France, to a political movement which could be influent enough to carry its whole society project? The environments of political economy, which were the authentic representatives of this wave, seemed to have had a hard time finding their place within a contentious context inherited from the French Revolution, but also fully investing in the game of democracy. As the defenders of free trade and limited state power, liberals also faced the increasing difficulty to see their ideas being questioned at the turn of the 20th century. It is thus necessary to go back to the very definition of French “classical” liberals, in order to better highlight their ambitions, their failures and their inherent practices, and better understand what constitute for them, and in many ways, their own identity.